Update of checklist of Digenean parasites of wild birds from Argentina, with comments about the extent of their inventory - Drago, Fabiana Beatriz (2015)
We present an update of the checklist of digenean parasites of birds from Argentina published by Lunaschi et al. (2007), including all additional records published since 2007 up to present and some records omitted in the preceding version. This new report includes information about 74 digenean taxa, distributed in 18 families and 45 genera, of which 68 species were reported parasitizing wild birds, 6 species were obtained experimentally, and 6 taxa identified at the generic level were recovered in wild birds and/or experimental host. Consequently, the actual number of digeneans recorded from Argentinean wild birds amounts 112 species in 65 genera of 20 families. The extension of this inventory was evaluated together with the number of hostparasite relations reported and the geographical distribution in the different ecoregions of the country. The species accumulation curve and the accumulation curve of host-parasite relations show that the inventory of digeneans of wild birds is far from being completed, even in the most studied areas. The taxonomic status of some species listed in Lunaschi et al. (2007), such as Lyperosomum oswaldoi, Parastrigea brasiliana, Lyperorchis inexpectabilis and Stephanoprora podicipei, was reconsidered according to new studies.